Genetic Improvement of Post-Heading Root Morphology and Physiology Facilitating Yield Increase of japonica Inbred Rice - Tianyao Meng; Xi Chen; Xubin Zhang; Jialin Ge; Guisheng Zhou; Qigen Dai; Huanhe Wei (Agronomy, 2021)
Since genetic improvement greatly promoted an increased yield japonica inbred rice in east China after the 1990s, better root characteristics were certainly expected. In 2018 and 2019, nine japonica inbred rice released in the 1990s, 2000s, and 2010s were investigated to evaluate the changes in root morpho-physiology and identify root traits that contributed to the positive yield trends during the genetic process. The 2010’s rice had 8.0 and 4.3% higher grain yield than the 1990’s and the 2000’s rice, respectively (p < 0.05). Genetic yield gain was mainly attributed to the increased spikelets per panicle. Compared with the 1990’s and the 2000’s rice, the 2010’s rice had higher shoot biomass at heading and maturity (p < 0.05), as well as root biomass (p < 0.05), especially for root biomass of 15–30 cm soil depth. Leaf area index (LAI), soil-plant analysis development (SPAD) values, and leaf photosynthetic rate at middle grain-filling period (MGP) and late grain-filling period (LGP) were all increased. The 2010’s rice had consistently higher root length and volume, root oxidation activity, and root bleeding rate at MGP and LGP than the 1990’s and the 2000’s rice (p < 0.05). Positive correlations were detected between root length and volume, root oxidation activity, and root bleeding rate at MGP, LGP, and SPAD values, leaf photosynthetic rate at MGP and LGP, and higher shoot biomass accumulation after heading and grain yield (p < 0.05 or p < 0.01). The present study implied that genetic improvement optimized post-heading root morphology and physiology, which maintained shoot stay-green and facilitated biomass accumulation and yield increase in japonica inbred rice during the genetic process since the 1990s.